Enhanced Training of Creative Specialists Based on the Advanced Education System Implementation - Eliseeva, Elena; Weiler, Veronika; Kuznetsova, Olga; Mishina, Mariya; Zverev, Alexey; Nazarova, Olga (International Journal of Economics and Financial Issues, 2016)
The paper analyzes the topical issue concerning training of creative specialists in the professional training system. The concept of advanced education, which allows to provide such new properties and qualities as portability, adaptability, continuity, innovativeness, creativity is considered as key in professional education restructuring. The paper covers a number of existing modern researches in the field of advanced education, offers the author's solution for the introduction of such system as "training for the future", for the "advanced" professional model construction, the implementation of advanced education courses. According to the concept of advanced education courses, the concept of advanced training courses for students (ATC), which focus on finishing the present professional training model constructing by adding the future professional competence, is introduced, thus, allowing to increase future specialists' competitiveness, to form full readiness to the chosen professional profile realization. The paper considers the role of supplementary education as the most important structure of the advanced professional training concept realization as an additional stimulant for the change of management and educational policy of professional education institutions towards well-defined restructuring strategies, the need for the professional training track reconsideration, the educational process quality change. Keywords: education, creative specialist, advanced education, advanced education courses JEL Classifications: P46, P50